Effectiveness of aerobic exercise in preventing gestational diabetes mellitus (GDM) among pregnant women: a systematic review - Abdul Rahman, Rozlin; Ayub, Ainon Atikah (IIUM Press, International Islamic University Malaysia, 2024)
Background: Gestational diabetes mellitus (GDM) is a rising global health issue, affecting both maternal and foetal health. It increases the risk of future type 2 diabetes in mothers and various complications in infants. Aerobic exercise has shown promise in preventing GDM by regulating blood glucose, reducing maternal weight gain, and improving insulin sensitivity. This systematic review evaluates the effectiveness of aerobic exercise in preventing GDM in pregnant women. Methodology: Multiple databases, including PubMed, Scopus, and ScienceDirect, were searched for studies published between 2010 and 2020. Randomized controlled trials (RCTs) assessing aerobic exercise as a preventive intervention for GDM were included. After applying the PICOS framework, 1,091 studies were identified, of which six met the inclusion criteria. Study quality was assessed using the revised Cochrane risk-of-bias tool. Results: Three studies showed significant improvements in fasting blood glucose and insulin sensitivity with aerobic exercise alone. However, results were mixed when aerobic exercise was combined with other modalities. The variation in findings can be attributed to differences in population risk factors, intervention duration, and study design. Conclusion: Aerobic exercise is a promising intervention for reducing GDM risk, particularly in high-risk populations. However, the variability in results highlights the need for standardized exercise guidelines regarding intensity, frequency, and duration. Future research should focus on clarifying these factors and exploring the combined effects of aerobic exercise with other interventions to further enhance GDM prevention.